The absolute method of neutron activation analysis using triga neutron reactor, nuclear agency, Malaysia - Liew, Hwi Fen (2010)
Neutron activation analysis (NAA) offers excellent sensitivities that are superior to other analytical techniques in performing identification and quantitative elemental analysis. The technique involves the irradiation of samples and the detection of gamma energies emitted from the isotopes formed from the process of neutron capture. Most NAA were done by comparison method, which is found to have high errors due to the differences in the matrix composition of sample as well as comparator. The purpose of this study is to demonstrate an alternative technique of activation analysis based on absolute gamma ray measurements and the direct calculation of elemental concentrations from reaction rates equation of neutron capture process. The efficiency of the gamma-ray spectrometer as well as the neutron spectrum parameters, thermal and epithermal neutron flux at four characterized irradiation position of 10, 22, 27, and 31 in the rotary rack 1-MW TRIGA reactor at Malaysia Nuclear Agency was determined. The accuracy and precision of this absolute NAA technique were verified by analyzing two certified reference materials, Soil-1 and Soil-7 provided by IAEA. The experimental results for both the materials irradiated at the four characterized irradiation positions were found to be in good agreement with the certified values. The average Z-score for the concentration values were below two signified that the concentration results were accepted for most elements. In conclusion, the proposed technique can be applied for many of future activation analyses with high accuracy without having to rely on the availability of standard samples.